Investigasi Hubungan Struktural Antara Cita Makanan, Kepuasan Makanan, Dan Kualitas Kuliner Terhadap Niat Berperilaku - Astia Aurelia Mustafa; Sujana Sujana (Jurnal Ilmiah Pariwisata Kesatuan, 2022)
This study aims to determine whether Food Image, Food Satisfaction, and Culinary Quality have partial and simultaneous effect on Behavioral Intentions. The population in this study are consumers who have visited the Culinary Tourism center of Bogor City with a total sample of 200 people. The sampling method used is a non-random sampling method. The data analysis method used is multiple linear regression analysis to determine the effect of Food Image, Food Satisfaction, and Culinary Quality on Behavioral Intentions. Data testing was carried out using IBM SPSS Statistics 24 Software. The results of this study are the results of the respondent's answer index table 4.6 Respondents' opinions of food image indicators with an average variable value of 3.84 which means high, table 4.7 respondents' opinions of food satisfaction indicators with an average variable value of 3.82 which means high Table 4.8 Opinions of respondents on the Culinary Quality indicator with an average variable value of 3.56 which means high, and table 4.9 Respondents opinion on behavioral intention indicators with the average variable value of 3.52 which means high. This shows that the Food Image, Food Satisfaction, and Culinary Quality and Behavioral Intentions are good, the company must maintain this situation and further improve, especially the food image so that the company gets more profit or more profits than the company has received before. In this study, it is known that the variables of Food Image, Food Satisfaction, and Culinary Quality have an effect of 55% on Behavioral Intentions and the remaining 45% is influenced by other aspects, so it is recommended for further researchers to explore other aspects that have not been discussed in this study. In addition, further researchers are also advised to increase the number of populations and samples so that the research results obtained can be even better. Keywords: Food Image, Food Satisfaction, Culinary Quality, and Behavioral Intentions